Changes in Eating Habits Due to the confinement of Covid-19 in the Peasant Community of Sapallanga 2021 - Martínez Véliz , Marivel Rosa (2022)
Objective: to determine the dietary changes due to the confinement of COVID-19 in the rural community of Sapallanga Huancayo 2021. Material and methods: it was a basic study, with a non-experimental design of a simple descriptive type of cross-section, the population consisted of by 2,045 adults and the sample was made up of 324 people, for this, simple random probability sampling was done, the technique used was the survey and the instrument was the questionnaire. Results: it was identified that the sociodemographic characteristics of the population of the rural community of Sapallanga Huancayo 2021. Age 30 to 40 years with 120 (37%) predominated, in males with 178 (54.9%), in the level of education was secondary with 121 (37.3%) and in the occupation as a worker with 228 (70.4%). In addition, it was identified that the changes in energy foods due to the confinement of COVID-19 in the population of the peasant community of Sapallanga Huancayo 2021. It has increased by 180 (55.5%), in consumption of construction foods has decreased in 160 (49.4%) and the consumption of protective foods has remained in 154 (47.5%). Conclusions: It has been determined that changes in eating habits due to the confinement of COVID-19 in the population of the community of Sapallanga Huancayo 2021, has increased the consumption of energy foods with 55.5%, has decreased the consumption of Builder foods with 49.4% and the consumption of protective foods with 47.5% has been maintained.